Field study of meeting thermal needs of occupants in old residential buildings in low-temperature environments using personalized local heating - Yang, Zhen (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
The outdated structures and heating devices in old residential buildings can no longer functionally meet the thermal needs of users and require reasonable supplementary measures to meet the demand. Personalized local heating, owing to its thermal comfort and energy-saving performance, is a good solution for addressing the thermal needs of occupants. The objective of this study was to examine the influence of personalized local heating on the thermal comfort of occupants in old residential buildings under low-temperature heating. A field study was conducted with 16 participants in typical old residential buildings under different conditions from January to February 2023. The findings revealed that all personalized local heating methods could increase the overall thermal sensation of participants at background temperatures of 16 degrees C and 19 degrees C, but only a few of them were effective in enhancing the participants' overall thermal comfort. Regardless of the chosen localized heating method, the participants' thermal acceptance vote varied over time. When using localized heating, there were differences in the body parts selected for heating among participants at 16 degrees C and 19 degrees C. The analysis showed that the corrective power of heating devices for human thermal comfort is related to the background environ-ment temperature, with stronger corrective power shown at lower temperatures. Furthermore, as long as the problem of uneven local heating was effectively resolved, radiant devices were the preferred environmental conditioning devices. This study provides important guidance, both for improving thermal comfort in old resi-dential buildings and for expanding the application of personalized local heating.